2012
DOI: 10.5402/2012/307102
|View full text |Cite
|
Sign up to set email alerts
|

Menadione : Sodium Orthovanadate Combination Eliminates and Inhibits Migration of Detached Cancer Cells

Abstract: Exposure of cancer cells to anticancer agents in cultures induces detachment of cells that are usually considered dead. These drug-induced detached cells (D-IDCs) may represent a clinical problem for chemotherapy since they may survive anoikis, enter the circulation, invade other tissues and resume proliferation, creating a metastasis, especially in tissues where the bioavailability of anticancer agents is not enough to eliminate all cancer cells. In this study we evaluated the antiproliferative effect of mena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
(60 reference statements)
0
5
0
Order By: Relevance
“…A combination of menadione and ascorbate resulted in oxidative stress-mediated cell death in liver cancer cells (Veerax et al, 2004). A combination of menadione and sodium orthovanadate eliminated and inhibited migration of detached cancer cells (Delwar et al, 2012). Combination of menadione with ethacrynic acid inhibited angiogenesis by down regulating vascular endothelial growth factor expression and blocking HIF-α interaction with p300 thereby inhibiting hypoxia in cancer cells (Na et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…A combination of menadione and ascorbate resulted in oxidative stress-mediated cell death in liver cancer cells (Veerax et al, 2004). A combination of menadione and sodium orthovanadate eliminated and inhibited migration of detached cancer cells (Delwar et al, 2012). Combination of menadione with ethacrynic acid inhibited angiogenesis by down regulating vascular endothelial growth factor expression and blocking HIF-α interaction with p300 thereby inhibiting hypoxia in cancer cells (Na et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…It has been investigated as a possible anti-tumor agent [52, 53]. Benzyl-β-nitroethene and derivatives have also been shown to be inhibitors of protein tyrosine phosphatases PTP1B and Yop [10, 12].…”
Section: Resultsmentioning
confidence: 99%
“…Sodium orthovanadate is a broad and highly active phosphatase inhibitor, as would be expected of a phosphate analog, and widely used as a PTP positive inhibitor control in enzyme assays. It has been investigated as a possible anti-tumor agent [ 52 , 53 ]. Benzyl-β-nitroethene and derivatives have also been shown to be inhibitors of protein tyrosine phosphatases PTP1B and Yop [ 10 , 12 ].…”
Section: Resultsmentioning
confidence: 99%
“…Compared with clofazimine, it appears that menadione, which is also known as vitamin K3, has attracted more attention from the perspective of cancer treatment. Menadione has been identified to exhibit significant therapeutic benefits in the treatment of gastric cancer ( 55 ), prostate cancer ( 56 ), oral cancer ( 57 ) and breast cancer ( 58 ). Furthermore, the latest research indicated that menadione may increase anticancer activity by combining ROS-generating agents ( 59 ), but how it works in ESCA treatment requires further investigation.…”
Section: Discussionmentioning
confidence: 99%